Dividend Payouts and Rollover Crises - Juelsrud, Ragnar E; Nenov, Plamen T (Review of Financial Studies, 2020)
Abstract We study dividend payouts when banks face coordination-based rollover crises. Banks in the model can use dividends to both risk shift and signal their available liquidity to short-term lenders, thus, influencing the lenders’ actions. In the unique equilibrium both channels induce banks to pay higher dividends than in the absence of a rollover crisis. In our model banks exert an informational externality on other banks via the inferences and actions of lenders. Optimal dividend regulation that corrects this externality and promote financial stability includes a binding cap on dividends. We also discuss testable implications of our theory. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online